Surface plasmon resonance detection of anti-cancer drug flutamide by graphitic carbon nitride/chitosan nanocomposite - Hassan Nasiri; Karim Abbasian (Scientific Reports)
Abstract The g-C3N4/CS biosensor was designed, fabricated, and tested using compounds such as glucose, urine, lactose, and flutamide at a molarity of 10 µM, which could demonstrate a high sensitivity of 200 μm-1 for flutamide. Powerful effective medium theory and FDTD simulation were used to predict the most favorable mode and plasmonic properties of a graphite carbon nitride and chitosan nanocomposite. The research also explores the characteristics of surface plasmon resonance exhibited by the nanocomposite as the chitosan content is adjusted. Subsequent simulations are conducted on nanocomposites incorporating a thin layer and a modified gold structure. The intricate simulations ultimately reveal the optimal combination, tested under three different pH conditions (6.2, 7.2, and 8). In acidic conditions, the kinetic profile yielded a KD= 3.45 × 10−7, surpassing the KD value of a thin film. The Au significantly outperformed the alternative material. The biosensor demonstrated linear behavior across a wide concentration range from 1 to 150 µM, achieving a detection limit of 120 nM with its high sensitivity.